Carbon Sequestration Potential of Traditional Agroforestry System in Rimbo Panjang Village, Kampar Based on Tree Biomass - Isda, Mayta Novaliza; Fatonah, Siti; Yulminarti, Yulminarti; Roslim, Dewi Indriyani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The traditional agroforestry industry is part of the Forestry and Other Land Use Net Sink 2030 (FOLU Net Sink 2030) strategy for low carbon development and climate resilience in Indonesia. This study aims to estimate the value of biomass, carbon stock, and carbon sequestration in traditional agroforestry systems in Rimbo Panjang Village, Kampar. Six plots (each measuring 20 x 20 meters) are used; three of the plots are 15 years old and three are 9 years old, respectively, for the conventional agroforestry system. Biomass, carbon stock and carbon sequestration were estimated at the tree, pole and sapling levels. Biomass calculations used allometric equations based on diameter at breast height (DBH) data. The results showed that carbon sequestration in Dusun 2 (618.2 tons/ha) was greater than in Dusun 1 (399 tons/ha), with an average carbon sequestration in both dusun of 508.6 tons/ha. Trees contribute the highest value of biomass, carbon stock, and carbon sequestration, which is 74%, The difference in the value of biomass, carbon stock, and carbon sequestration in traditional agroforestry systems in Rimbo Panjang Village is significantly influenced by the average stem diameter. The various trees that make up traditional agroforestry in Rimbo Panjang Kampar, which is generally in the yard, should ideally be maintained and developed because of their high carbon sequestration potential.